Forensic genetic analysis of bio-geographical ancestry. (September 2015) - Phillips, Chris
Highlights: The review outlines some of the current understanding of past human population structure and how it may have influenced the complex distribution of contemporary human diversity. A simplified description of human diversity can provide a suitable basis for choosing the best ancestry-informative markers, a necessary compromise given the constraints of multiplex sizes in forensic DNA tests. A detailed comparison is made of the most informative ancestry markers suitable for forensic use. Assessments are made of the data analysis regimes that can provide statistical inferences of a DNA donor's bio-geographical ancestry. Abstract: With the great strides made in the last ten years in the understanding of human population variation and the detailed characterization of the genome, it is now possible to identify sets of ancestry informative markers suitable for relatively small-scale PCR-based assays and use them to analyze the ancestry of an individual from forensic DNA. This review outlines some of the current understanding of past human population structure and how it may have influenced the complex distribution of contemporary human diversity. A simplified description of human diversity can provide a suitable basis for choosing the best ancestry-informative markers, which is important given the constraints of multiplex sizes in forensic DNA tests. It is also important to decide the level of geographic resolution that is realistic to ensure the balance between informativeness and an over-simplification of complex human diversity patterns. A detailed comparison is made of the most informative ancestry markers suitable for forensic use and assessments are made of the data analysis regimes that can provide statistical inferences of a DNA donor's bio-geographical ancestry.